Institutionalizing Agonistic Democracy : Post-Foundationalism and Political Liberalism. - Wingenbach, Ed (Rethinking political and international theory., 2011)
Contemporary politics are characterised by the impossibility of agreement on fundamental values. This book examines the institutional alternatives available to democratic politics to determine which institutional structures are most likely to produce a democratic social order in which agonistic citizenship might flourish.